The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/jobm.200610255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inoculation with Penicillium albidum, a phosphate‐solubilizing fungus, on the growth of Trifolium pratense cropped in a volcanic soil

Abstract: Volcanic soils in the south of Chile have an elevated quantity of total P, which is scarcely available due to its high P fixation capacity. One strategy for increasing the availability of P for the vegetables that grow there would be to use phosphate-solubilizing microorganisms. In one assay conducted in a greenhouse on a volcanic soil, the effect of inoculation with Penicillium albidum, a phosphate-solubilizing fungus, was studied on the growth of red clover (Trifolium pratense L). Some chemical and biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Phosphatases catalyze the hydrolysis of organic P-compounds, such as esters and anhydrides of orthophosphoric acid, and do not solubilize rock phosphates [17]. This enzyme is important in soil, in particular for the Andisols, where the P is limiting for vegetable development, and our results agrees with those obtained by other authors in previous studies [38,39]. This can be attributed to the increase in microbial biomass activity in the inoculated soil.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Phosphatases catalyze the hydrolysis of organic P-compounds, such as esters and anhydrides of orthophosphoric acid, and do not solubilize rock phosphates [17]. This enzyme is important in soil, in particular for the Andisols, where the P is limiting for vegetable development, and our results agrees with those obtained by other authors in previous studies [38,39]. This can be attributed to the increase in microbial biomass activity in the inoculated soil.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted by Morales et al [38] in an Ultisol soil showed that inoculation with Penicillum albidum significantly affects P in both plant and roots. In addition, Turan et al [39] reported increases in P in plant tissues inoculated with Bacillus magaterium.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the increase in available P in the soil with the application of G. pannorum and P. carneus were comparable to those obtained with the fungal strains currently used in organic fertilizers (Morales et al, 2007;Mittal et al, 2008;Kaewchai et al, 2009), making them good candidates for field-level testing.…”
Section: Discussionsupporting
confidence: 86%
“…as the more often described genera (Silva Filho et al, 2002;Morales et al, 2007). Inoculation with phosphatesolubilizing fungi enhanced plant growth and increased P uptake by the plants, both under greenhouse and field conditions (Asea et al, 1988;Whitelaw, 2000;Wakelin et al, 2004;Morales et al, 2007).…”
Section: Introductionmentioning
confidence: 92%
“…With regard to those microorganisms able to release available P from sparingly soluble P-sources most published information refers to bacteria, but there are several reports concerning fungi (Morales et al, 2007;Barroso and Nahas, 2007), with Penicillium and Aspergillus spp. as the more often described genera (Silva Filho et al, 2002;Morales et al, 2007).…”
Section: Introductionmentioning
confidence: 99%